3D Printing in Construction: Current Status, Implementation Hindrances, and Development Agenda - Xin Ning; Tong Liu; Chunlin Wu; Chao Wang (Advances in Civil Engineering)
3D printing (3DP) is regarded as an innovation that contributes to automation in civil engineering and offers benefits in design, greenness, and efficiency. It is necessary to objectively analyze the current status and challenges associated with 3DP and identify future research directions to properly understand its construction applications. Previous research has focused more on the technical dimension of 3DP; however, the nontechnical dimension of the technology may hinder its implementation and thus must be paid particular attention to. This study presents a systematic review of the existing literature from both technical and nontechnical dimensions by combining quantitative and qualitative studies. The quantitative study was conducted using scientometric methods. The qualitative study analyzed information, including the technical research status and nontechnical challenges and trends. Two aspects of technical research status are presented, including materials and processes. In addition, nontechnical challenges and trends from the economic, environmental, social, and legislative aspects are proposed. This study provides a comprehensive agenda to advance 3DP in construction and proposes research interests, challenges, and future topics. It is intended to help construction practitioners systematically master existing processes and materials and assess the application degree and necessity of 3DP.